PENINGKATAN KUALITAS PENDIDIKAN MELALUI MODEL PEMBELAJARAN KOOPERATIF BERBASIS KONSTRUKTIVISTIK - Suhardiyanto, Andi (Lembaran Ilmu Kependidikan, 2009)
One of the recent main instructional problems at schools is the studentsÃ¢â¬â¢ lowachievement as shown by the very poor average result. One of the causing factors isthe instruction which is still conventional and teacher centered. Therefore, theinstruction does not touch the students. This means it does not really consider howlearning actually takes place. The implementation of the Competence BasedCurriculum which was then revised with the School Based Curriculum requires aparadigm change in education in the learning process at schools. The change is inessence to improve the quality of education in terms of the process and result. One ofthe efforts is the change of the teaching style with a more innovative instructionalmodel. Constructivism-based cooperative learning is one of alternatives which can beused. The constructive learning concept emphasizes the students to construct newknowledge with the preexisting knowledge. Cooperative learning is oriented towardschildrenÃ¢â¬â¢s knowledge building through group works. It is hoped that with theconstructivism-based cooperative learning model students will further optimize theirskill in the learning process.Kata kunci : kualitas, pembelajaran kooperatif, dan konstruktivistik